Income Distribution, Inequality and Unemployment - Uwe Wagschal (Luxembourg Income Study (LIS), 1997)
This study deals with unemployment and employment and its relations with income distribution and related subjects. Massive changes in earnings inequality and income distribution in the OECD during the 80s and 90s, as well as huge variations in the development of unemployment and employment figures are discussed. The author's objective is to address, Are there any systematic relations between income inequality and labor market indicators and, moreover, which common factors caused these changes? Which political climate and institutions are favorable to such a change?
Keywords: 330; Einkommensverteilung; Arbeitslosigkeit; OECD-Staaten